Zdravstvena nega pacienta, ki je samomorilno ogrožen - Vršnik, Petra (Obzornik zdravstvene nege, 2020)
Introduction: The role of a nurse in the treatment of patients who are at a risk of suicide is one of the key factors in suicide prevention. The purpose of the study was to review the literature dealing with nursing of patients at a risk of suicide in Slovenia and abroad. Methods: A systematic literature review was conducted in databases PubMed, CINAHL, Google Scholar andthe Slovenian Nursing Review from March 2018 to September 2018. Advanced search was conducted with the Boolean operator AND, and the following key words: "psychiatric nursing care", "the role of nurses", "nurse prevention suicide", "suicidal patients" and "mental health nursing". In Slovenian the key word "samomor" was used. Of 2101 search results, 17 sources or articles were included in the qualitative content analysis. Results: The articles are classified according to identified codes in the category: "a nurse's role and the importance of nursing" that is divided into four sub-categories: (1) Nursing activities or activities for prevention of suicide, (2) Therapeutic attitude and communication of a nurse with a patient at a risk of suicide, (3) A nurse's problems in dealing with a patient at a risk of suicide and (4) Actions to improve treatment and prevent suicide. Discussion and conclusion: Nurses are likely to encounter patients who have suicidal thoughts in all areas of their practice. Nurses can affect patients' well-being with the manner in which they take care of them and respond to their distress. To work efficiently, nurses should obtain special knowledge on identifying, evaluation and prevention of suicide
Keywords: duševno zdravje; medicinske sestre; mental health; nurses; psihiatrija; psychiatry; safety; suicid; suicide; varnost